Identifying Students’ Misconceptions in Chemical Equilibrium Using a Five-Tier Multiple-Choice Diagnostic Test - Putri Adita Wulandari; Muhammad Fikri; Abdullah Abdullah; Tiara Swastika Putri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2026)
This study aims to identify the profile of students' misconceptions on chemical equilibrium and to determine the sources of these misconceptions. This study used a descriptive method with quantitative and qualitative approaches and was conducted at SMA Negeri 7 Pekanbaru. The research subjects involved 187 11th-grade students who had studied chemical equilibrium. Data collection was conducted using a five-level diagnostic test instrument consisting of 15 questions and structured interviews. The results showed that the average percentage of students experiencing misconceptions was relatively low, at 20.93%. Analysis of the sources of misconceptions showed that the main cause of misconceptions came from students' personal thoughts, with a percentage of 24.15%. Other contributing sources included friends (20.66%), teachers (18.78%), the internet (18.35%), and books (18.06%). These findings indicate that students' misconceptions are more influenced by independent constructions of understanding that do not align with scientific concepts than other external factors.